2013
DOI: 10.3390/f4040868
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Relationship between Urban Park Characteristics and Park Cool Island Intensity by Remote Sensing Data and Field Measurement

Abstract: The cooling effects of urban parks, which form “Park Cool Island” (PCI), can help decrease land surface temperature (LST) and mitigate urban heat island (UHI) effects. PCI intensity largely depends on the characteristics of urban parks. The relationship between PCI intensity and urban park characteristics such as urban park size has been well documented. However, it is still unclear how urban forest structures in parks affect PCI intensity and particularly whether the relationship changes across seasons. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(94 citation statements)
references
References 41 publications
4
84
0
6
Order By: Relevance
“…The decrease in community body size was only significant for built-up area assessed in the immediate surroundings of the pond (50-200 m radius). This most likely reflects built-up area in the immediate vicinity of the pond being the best predictor of extreme temperatures, while parks and large gardens in the cities experience somewhat cooler temperatures [48][49][50]. We, however, found that cladoceran communities characterized by a relatively high relative abundance (more than 5%) of large-bodied species displayed a different pattern.…”
Section: Discussionmentioning
confidence: 63%
“…The decrease in community body size was only significant for built-up area assessed in the immediate surroundings of the pond (50-200 m radius). This most likely reflects built-up area in the immediate vicinity of the pond being the best predictor of extreme temperatures, while parks and large gardens in the cities experience somewhat cooler temperatures [48][49][50]. We, however, found that cladoceran communities characterized by a relatively high relative abundance (more than 5%) of large-bodied species displayed a different pattern.…”
Section: Discussionmentioning
confidence: 63%
“…Covering approximately 524 km 2 (within the beltway) (Figure 1), Changchun had 3.659 million inhabitants at the end of 2014 (Changchun Statistical Bureau data). The climate is temperate humid or sub-humid continental monsoon, the mean annual precipitation is 567 mm, and the mean air temperature is 4.8 • C [26]. Dominant soil types are black soil, dark-brown soil, and chernozem [27].…”
Section: Study Area Description and Urbanization Level Classificationmentioning
confidence: 99%
“…LST shows significant correlation with air temperature and provides complete spatial coverage across an entire cityscape Klok, Zwart, Verhagen, & Mauri, 2012;. Extensive research has explored relationships between SUHI and urban land cover, especially with regard to vegetation (Buyantuyev & Wu, 2010;Li, Li, Middel, Harlan, & Brazel, 2016;Myint, Wentz, Brazel, & Quattrochi, 2013;Ren et al, 2013;Weng 2009;. Studies have suggested that land cover composition and configuration of the green space are strong predictors of its cooling effect (Cao, Onishi, Chen, & Imura, 2010;Li et al, 2013;Lin, Yu, Chang, Wu, & Zhang, 2015;Maimaitiyiming et al, 2014;Ren et al, 2013Ren et al, 2013.…”
Section: Introductionmentioning
confidence: 99%